Running Text Information System Design Internet-Based for Small Outlets - Nanik Triwahyuni; Samuel Beta (Politeknik Negeri Semarang, 2022)
Currently, there are many small business outlets that have opened branches in many places. With the spread of outlets that are far apart, it becomes a problem for the owner to be in a certain place on a display board that is installed at a height in each of his outlets. Display boards that are commonly used as promotional media and usually show product prices/interesting information are running text boards. In some studies there are those who make ESP as an access point, so that it can only be accessed within the range of the access point. So it cannot be accessed remotely. To facilitate this information, in this study, we designed an internet-based mobile text information system using the ESP32 Microcontroller and the Message Queuing Telemetry Transport (MQTT) protocol, as well as a display board (DMD LED Panel P10). By using an android-based mobile device that is owned by almost everyone and then equipped with the MQTT application, it is hoped that information will no longer be constrained by distance and the absence of a computer device, as well as the limited number of computer operators.